Corporate Philanthropy and Productivity: Evidence from an Online Real Effort Experiment - Mirco Tonin; Michael Vlassopoulos (Center for Economic Studies and ifo Institute (CESifo), 2014)
Contributing to a social cause can be an important driver for workers in the public and non-profit sector as well as in firms that engage in Corporate Philanthropy or other Corporate Social Responsibility policies. This paper compares the effectiveness of social incentives - that take the form of a donation received by a charity of the subject's choice - to financial incentives. We find that social incentives lead to a 13% rise in productivity, regardless of their form (lump sum or related to performance) or strength. The response is strong for subjects with low initial productivity (30%), while high-productivity subjects do not respond. When subjects can choose the mix of incentives half sacrifice some of their private compensation to increase social compensation, with women more likely than men. Furthermore, offering subjects some discretion in choosing their own payment scheme leads to a substantial improvement in performance. Comparing social incentives to an equally costly increase in private compensation for low productivity subjects reveals that the former are less effective in increasing productivity, but the difference is small and not statistically significant.
Keywords: D64; J24; J32; L30; M14; M52; 330; financial incentives; social incentives; prosocial behavior; real effort experiment; corporate philanthropy; corporate social responsibility; gender